2022
DOI: 10.3390/su14137818
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Effect of the Interaction between Fintech and the Real Economy Based on Tail Risk Dependent Structure Analysis

Abstract: Fintech innovation has greatly improved the operation efficiency of the financial industry and promoted the sustainable development of the real economy. On the other hand, fintech also brings the problem of risk spillover. Through a time series analysis, vector auto-regression with the Granger causality test is conducted to analyze the interaction between fintech and the real economy. To deal with the nonlinear relationship and overcome the high-dimensional-dependent structure faced by Copula, this paper estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…International researchers such as Chiu, Pena, and Wang [47], Silva, Alexandre, and Tabak [50], and Brunnermeier, Dong, and Palia [51] have confirmed the volatility spillover between the financial sector and real industries, emphasizing its significance. Chinese scholars such as Peng [52], Zhu [53], Cao [54], and Li [55] have conducted in-depth discussions on the risk spillover relationship between the two based on different data samples and models.…”
Section: Spillover In the Real Economy Real Estate Market And Financi...mentioning
confidence: 99%
“…International researchers such as Chiu, Pena, and Wang [47], Silva, Alexandre, and Tabak [50], and Brunnermeier, Dong, and Palia [51] have confirmed the volatility spillover between the financial sector and real industries, emphasizing its significance. Chinese scholars such as Peng [52], Zhu [53], Cao [54], and Li [55] have conducted in-depth discussions on the risk spillover relationship between the two based on different data samples and models.…”
Section: Spillover In the Real Economy Real Estate Market And Financi...mentioning
confidence: 99%
“…There are many types of FinTech companies in the world, and they play different roles. In China, due to strict lending licenses, FinTech companies mainly play the role of helping lenders in the financial market with information gathering, screening, and decision-making; as mentioned in the introduction, they play a crucial role with respect to financial institutions due to the "technology spillover effect" [8]. Referring to Xie and Zhu (2021) [54], we set city-level FinTech development as the explanatory variable.…”
Section: Explanatory Variable: Fintechmentioning
confidence: 99%
“…On the one hand, it brings a shock to traditional commercial banks, causing them to lose substantial borrowers and reducing profits from the lending business, called the "competitive effect" [7]. On the other hand, FinTech can perform a "technology spillover effect", using information technology to create new opportunities for traditional banks and alleviate information asymmetry and low efficiency of loan allocation [8]. However, in China's financial system, not all FinTech players can obtain a loan license from a strict regulatory body.…”
Section: Introductionmentioning
confidence: 99%
“…The research found that risk in fintech can have an extreme impact on industry in a short time. Gupta et al [27] conducted a study on office real estate from the perspective of remote work and found that the impact of the pandemic on lower quality office buildings was greater than that on higher quality office buildings. Samitas et al [28] investigated the spread of the Subprime Crisis and the European Sovereign Debt Crisis from Eurozone countries to the real economy.…”
Section: Literature Review and Interplay Among Industriesmentioning
confidence: 99%